2018
DOI: 10.1111/cpf.12545
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing for evaluation of a randomized exercise training intervention following aortic valve replacement

Abstract: Summary Aortic valve surgery is the definitive treatment for aortic stenosis ( AS ). No specific recommendation is available on how exercise training should be conducted and evaluated after aortic valve replacement ( AVR ). This study aimed to examine the effect of aerobic exercise training on exercise capacity following AVR . In addition to our primary outcome variable, peak oxygen uptake (peak VO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Furthermore, the maximal oxygen uptake (VO2 max) demonstrated a parallel negative correlation trend with fat mass (R-0.42692), with a linear correlation coefficient of R = −0.42692. These correlations align with findings from the existing literature, indicating that VO2 max is associated with better body composition while being negatively related to the adipose component [6,21,22]. This represents a novel aspect not previously reported in studies, especially within the transplant population.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the maximal oxygen uptake (VO2 max) demonstrated a parallel negative correlation trend with fat mass (R-0.42692), with a linear correlation coefficient of R = −0.42692. These correlations align with findings from the existing literature, indicating that VO2 max is associated with better body composition while being negatively related to the adipose component [6,21,22]. This represents a novel aspect not previously reported in studies, especially within the transplant population.…”
Section: Resultssupporting
confidence: 89%
“…Lifestyle reconditioning is important to reduce cardiovascular risk factors in many metabolic chronic diseases, including post-transplantation. Changes, especially in cardiorespiratory function and metabolic profile, have been largely observed in the presence of comorbidities, like coronary artery disease, hypertension, and diabetes, and also posttransplantation [1][2][3][4][5][6][7][8][9][10][21][22][23]; however, other specific determinants, such as the body composition parameters, have not been yet investigated. Prolonged sedentarism and potential cardiotoxicity due to the long-term immunosuppression therapy increase the eventual impairment of the system-diastolic function, reducing the cardiorespiratory performance and the possibility of following constant training.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the efficacy and safety of exercise-based CR, a randomized pilot trial has shown that an 8-week moderate combined endurance and strength training was safe, with no adverse effects on valve prosthesis, kidney, or neurohumoral function ( 58 ), and was able to improve long-term oxygen consumption at anaerobic threshold (VO 2 AT). However, peak VO 2 , muscle strength, or quality of life was unchanged ( 59 ), which contradicts findings from several other studies demonstrating that post-operative exercise was able to improve peak VO 2 ( 60 62 ), though a longer follow-up period may be required to fully confirm the effects of exercise training on muscle strength and other quality of life indicators. Nevertheless, despite the risk of post-exercise complications, such as arrhythmias, musculoskeletal injuries, or chest pain, patients after TAVR can undergo CR safely and successfully if monitored and guided by rehabilitation physicians ( 61 ).…”
Section: Cr Use In Tavrcontrasting
confidence: 70%
“…Our results are comparable to those of other phase-II CR studies reporting improvements in 6MWD [12,[24][25][26][27][28][29][30] after 3-4 week CR. Other studies show that improvements in VO 2 peak are to be expected in outpatient programs with longer duration [29,[31][32][33][34]. The improvements in physical performance did not reveal significant differences between groups.…”
Section: Discussionmentioning
confidence: 74%